Trapped antihydrogen - Dirk van der Werf (Hyperfine Interactions, 2012)
Precision spectroscopic comparison of hydrogen and antihydrogen holds the promise of a sensitive test of the Charge-Parity-Time theorem and matter-antimatter equivalence. The clearest path towards realising this goal is to hold a sample of antihydrogen in an atomic trap for interrogation by electromagnetic radiation. Achieving this poses a huge experimental challenge, as state-of-the-artmagnetic-minimum atom traps have well depths of only ~1 T (~0.5 K for ground state antihydrogen atoms). The atoms annihilate on contact with matter and must be ‘born’ inside the magnetic trap with low kinetic energies. At the ALPHA experiment, antihydrogen atoms are produced from antiprotons and positrons stored in the form of non-neutral plasmas, where the typical electrostatic potential energyper particle is on the order of electronvolts, more than 10^4 times the maximum trappable kinetic energy. In November 2010, ALPHA published the observation of 38 antiproton annihilations due to antihydrogen atoms that had been trapped for at least 172 ms and then released—the first instance of a purely antimatter atomic system confined for any length of time (Andresen et al., Nature 468:673, 2010). We present a description of the main components of the ALPHA traps and detectors that were key to realising this result. We discuss how the antihydrogen atoms were identified and how they were discriminated from the background processes. Since the results published in Andresen et al. (Nature 468:673, 2010), refinements in the antihydrogen production technique have allowed many more antihydrogen atoms to be trapped, and held for much longer times. We have identified antihydrogen atoms that have been trapped for at least 1,000 s in the apparatus (Andresen et al., Nature Physics 7:558, 2011). This is more than sufficient time to interrogate the atoms spectroscopically, as well as to ensure that they have relaxed to their ground state